If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 1 = 3(6x + -7) Reorder the terms: 1 + 7x = 3(6x + -7) Reorder the terms: 1 + 7x = 3(-7 + 6x) 1 + 7x = (-7 * 3 + 6x * 3) 1 + 7x = (-21 + 18x) Solving 1 + 7x = -21 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 1 + 7x + -18x = -21 + 18x + -18x Combine like terms: 7x + -18x = -11x 1 + -11x = -21 + 18x + -18x Combine like terms: 18x + -18x = 0 1 + -11x = -21 + 0 1 + -11x = -21 Add '-1' to each side of the equation. 1 + -1 + -11x = -21 + -1 Combine like terms: 1 + -1 = 0 0 + -11x = -21 + -1 -11x = -21 + -1 Combine like terms: -21 + -1 = -22 -11x = -22 Divide each side by '-11'. x = 2 Simplifying x = 2
| 2s+6=s+13 | | 10x^2-6=7x | | x+-0.05x+1=1+11.95x | | (5-3x)(2+4x)= | | 6m+4=5m-1 | | -2[8-5(2-3x)-7x]=4(x+9) | | x+-0.05x+11.95x=1-1 | | X=(2x^2+3x-6)+(x^2-18x+6) | | 4x^2+3x-6=0 | | 6x^2-6x+10=2x^2-2x+25 | | x-0.5(0.1x-2)=1+11.95x | | -9x+3x=-24 | | 8x(3x+2)=-5(2-x)+3 | | 1270=.15x | | -5x-13x+3x=-25 | | -5x-13x+3x=25 | | 2x+y-4= | | 3+5m-4-8m=-8(m-3)+2(m-8) | | 8-3=5 | | 2+2-2=2+2-2+2 | | 24*x=96 | | 24xy=96 | | y(y+1)=20 | | (x+5)(x+5)=16 | | 9(c-1)=6(b+2)-a | | 77.94-5.8+201.681= | | 2x^2-36x+162=32 | | 10a^2-27ab+5b= | | 9(n-1)=6(n+2) | | x-7=3x | | 3(x+4)=(3x+12) | | 9x-1(4x-1)=2 |